Pyrolysis mucilage glue, preparation method and application of pyrolysis mucilage glue in electrolytic film cutting part
By using modified polyacrylate resin in the thermolytic adhesive, the thermal degradation characteristics of tert-butyl ester and tert-butoxycarbonyl group are used to achieve directional peeling of the glue at a lower temperature, and the thermolytic adhesive in the prior art is solved. Problems of water residue and degumming.
Patent Information
- Application Number
- CN202411642779.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-18
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-11-18
AI Technical Summary
Existing thermolytic adhesives are prone to residual after peeling, and thermal expansion additives may remain on the substrate surface, resulting in risk of degumming.
Modified polyacrylate resin, containing tert-butyl ester and tert-butyloxycarbonyl, is used to achieve directional peeling at lower temperatures through thermal degradation mechanism to reduce the risk of residual glue.
The glue peeling is effectively achieved at a lower temperature, avoiding degumming and significantly reducing the probability of residual glue.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of adhesives, and in particular to a pyrolytic adhesive, a preparation method and application thereof in electrolytic membrane cutting. Background Art
[0002] Pressure-sensitive adhesive is a widely used adhesive material. When pressure-sensitive adhesive is pasted to the surface of an object and pressure is applied, it will infiltrate the surface of the object and achieve strong adhesion through the interaction force between molecules. According to different usage requirements, the mechanical properties of pressure-sensitive adhesives are also different, among which peel force is a key indicator. The adhesion of the tape determines its application scenario: tapes with high adhesion are suitable for permanent bonding, while tapes with low peel force are suitable for temporary bonding, and a balance needs to be found between maintaining adhesion and easy removal. With the development of manufacturing technology, new processing technologies have put forward higher requirements on the performance of pressure-sensitive adhesives. Not only does the pressure-sensitive adhesive need to be firmly adhered to the substrate, but it is also required to be easily peeled off after use, or to provide remedies for incorrect operations during processing. Therefore, the viscosity-reducing viscoelastic film (also called viscosity-reducing pressure-sensitive adhesive, viscosity-reducing tape or debonding tape) came into being. This material is prepared by coating a viscosity-reducing viscoelastic on a polyester film, and the viscosity-reducing viscoelastic needs to add a switch that can respond to external stimuli (such as light, heat, pH value, solvent, etc.). In the initial state, the viscosity-reducing viscoelastic film has a high bonding strength, but its bonding strength decreases rapidly after responding to external stimuli. This material has a wide range of applications in many fields, such as medical wound dressings and the processing of ultra-thin and tiny devices.
[0003] The key to the development of debonding products is to have appropriate peeling force before stimulus response. In order to ensure that the tape does not fail during use, the peeling force before stimulus response is usually as high as possible. In order to better peel off the product, the peeling force after stimulus response is as low as possible. However, high peeling force before response and low peeling force after response are contradictory properties. It is easy to lose sight of one while focusing on the other in product design, which also increases the difficulty of product design. At present, UV response and thermal response are the main debonding products. UV irradiation is widely used because of its advantages such as low energy, simple operation and easy storage of products. Thermal response solves the defect that some application scenarios cannot be transparent. Thermal debonding includes thermal expansion debonding or thermal degradation debonding, shape memory or thermal phase change.
[0004] CN115093813A provides a thermal viscosity-reducing adhesive, including 10 to 100 parts of acrylic pressure-sensitive adhesive, 2 to 10 parts of foaming agent, 0.1 to 5 parts of curing agent, 0.1 to 4 parts of polysiloxane, and 50 to 60 parts of solvent. A thermal viscosity-reducing protective film is also provided, and the thermal viscosity-reducing protective film includes a substrate layer, a release layer, and a thermal viscosity-reducing adhesive layer formed by the thermal viscosity-reducing adhesive. The thermal viscosity-reducing adhesive provided by the invention is lubricated by introducing polysiloxane, so that residues can be effectively prevented from being left on the flexible circuit board during the removal of the thermal viscosity-reducing protective film. In addition, the viscosity of the thermal viscosity-reducing adhesive is greatly reduced after heating, so that the thermal viscosity-reducing protective film can be easily removed. Therefore, the invention solves the problem of low work efficiency and easy residues left on the circuit board in the process of removing the thermal viscosity-reducing protective film adhered to the flexible circuit board.
[0005] CN118389098A discloses a heat-reduced viscosity polyacrylate pressure-sensitive adhesive and a preparation method thereof. The heat-reduced viscosity polyacrylate pressure-sensitive adhesive is obtained by uniformly mixing a polyacrylate solution, a fluorine-modified acrylic rosin resin, a composite foamed microsphere and a cross-linking agent, and then coating and drying. The method introduces fluorine-containing monomers into the tackifying resin and the foamed microspheres, and utilizes the migration characteristics of the fluorine-containing chain segments during the heating process, which is beneficial to the migration of the tackifying resin and the foamed microspheres to the bonding surface, improves the heat-reduced viscosity efficiency, and prevents the problem of residual adhesive of the pressure-sensitive adhesive during the heat-reduced viscosity. At the same time, by controlling the amount of the fluorine-containing chain segments, it is ensured that the system has good bonding performance, solves the problems of low efficiency and easy residual adhesive of the heat-reduced viscosity pressure-sensitive adhesive, and obtains a heat-reduced viscosity polyacrylate pressure-sensitive adhesive with excellent performance.
[0006] The thermally viscous protective film formed by adding expandable foam to the current pyrolysis station adhesive has a good effect on circuit boards or electronic components. When the pyrolysis adhesive is at a certain temperature, the expandable foam expands, which reduces the viscosity of the glue, making the protective film easy to peel off. However, due to the presence of the foaming agent in this protective film, there will be different degrees of residue after peeling, which still needs to be removed manually or by machine, which is time-consuming and labor-intensive. Summary of the invention
[0007] In view of the above-mentioned defects of the prior art, the technical problem to be solved by the present invention is to provide a pyrolytic adhesive water, a preparation method and an application thereof in electrolytic membrane cutting.
[0008] When adding heat-sensitive expansion materials to the glue, the temperature of the glue rises, causing the heat-sensitive expansion materials to expand and increase in volume, thereby reducing the effective contact area with the adhered object and reducing the peel strength. However, as a nanomaterial, the heat-expanding additive is easy to remain on the surface of the substrate, resulting in residual glue. Compared with thermal expansion debonding, thermal degradation debonding reduces the modulus and molecular weight of the adhesive, resulting in a decrease in its bonding strength. It does not require the participation of additives. Thermally degradable materials include polyperoxides and azo compounds. There are also carbamates, carbonates, acetals, acetal esters and esters. High temperature causes thermal cleavage of covalent bonds, reducing the crosslinking density and thus causing debonding. As a heat-degradable bond, the ester bond has a thermal degradation ability that decreases from tertiary esters to secondary esters to primary esters. However, when thermal debonding glue is used in electronic components, too low a thermal degradation temperature will cause the glue to debond at an inappropriate time. Therefore, the present invention provides a modified polyacrylic acid ester resin, which contains tert-butyl ester and tert-butyloxycarbonyl, wherein the tert-butyl ester has a higher thermal degradation ability, but the thermal degradation of the tert-butyloxycarbonyl group requires a relatively high temperature, so the obtained modified polyacrylic acid resin is not easy to debond at a lower temperature, which avoids the debonding of the glue and can achieve directional peeling.
[0009] To achieve the above object, the present invention provides a pyrolytic adhesive comprising the following components in parts by weight: 90-95 parts of modified polyacrylic acid resin, 15-35 parts of tackifying resin, 1-3 parts of curing agent and 80-85 parts of solvent.
[0010] The preparation method of the modified polyacrylate resin comprises the following steps:
[0011] X1. Add hydroxyethyl acrylate, di-tert-butyl dicarbonate and 4-dimethylaminopyridine to toluene, stir at room temperature for 18-26 hours, add chloroform to dilute, and wash with dilute hydrochloric acid. After separation, the organic phase is dried, concentrated and purified by column to obtain the modified monomer;
[0012] X2. Add the modified monomer, tert-butyl acrylate, isooctyl acrylate and azobisisobutyronitrile to anisole, heat and polymerize under an inert atmosphere, and purify by column after 2 to 4 hours to remove impurities and solvents to obtain modified polyacrylic acid resin.
[0013] Furthermore, the molar ratio of the hydroxyethyl acrylate to di-tert-butyl dicarbonate and 4-dimethylaminopyridine is 1:1-2:0.1-0.2.
[0014] Furthermore, the molar ratio of the modified monomer to tert-butyl acrylate, isooctyl acrylate and initiator is 5-9:5-9:4-10:0.1-0.2.
[0015] Furthermore, the temperature range of the temperature-raising polymerization is 60-80°C.
[0016] Furthermore, the amount of toluene used is 0.5 to 2 times the total volume of hydroxyethyl acrylate, di-tert-butyl dicarbonate and 4-dimethylaminopyridine.
[0017] Furthermore, the amount of chloroform used is 2 to 6 times the volume of toluene.
[0018] Furthermore, the amount of anisole used is 2 to 4 times the total volume of the modified monomer, tert-butyl acrylate, isooctyl acrylate, and azobisisobutyronitrile.
[0019] Furthermore, the tackifying resin is one of terpene and its derivative resins, rosin and its derivative resins.
[0020] Furthermore, the curing agent is one of an isocyanate curing agent and an epoxy curing agent.
[0021] Furthermore, the solvent is one of ethyl acetate, toluene or isopropanol.
[0022] A method for preparing pyrolytic adhesive water comprises the following steps:
[0023] The modified polyacrylic acid resin, tackifying resin, curing agent and solvent are uniformly mixed to obtain pyrolytic adhesive.
[0024] The present invention also provides an application of pyrolytic adhesive water in electrolytic membrane cutting, specifically, the pyrolytic adhesive water is coated on the surface of aluminum foil.
[0025] Beneficial effects of the present invention:
[0026] Compared with the prior art, the present invention provides a modified polyacrylic acid ester resin, which contains tert-butyl ester and tert-butyloxycarbonyl, wherein the tert-butyl ester has a higher thermal degradation ability, but the thermal degradation of the tert-butyloxycarbonyl requires a relatively high temperature, so the obtained modified polyacrylic acid resin is not easy to debond at a lower temperature, which avoids the debonding of the glue and can achieve directional peeling. DETAILED DESCRIPTION
[0027] Terpene resin, T-120, softening point ≥120, saponification value ≤1.5 mgKOH / g, iodine value 40-75, Shenzhen Yoshida Chemical Co., Ltd.
[0028] Isocyanate curing agent, brand HB175 MP / X, NCO content 16%-17%, BASF.
[0029] The invention provides a pyrolytic adhesive, which is prepared from modified polyacrylic acid resin, tackifying resin, curing agent and solvent.
[0030] Modified polyacrylic resin is the matrix of adhesive and provides the main bonding performance. It plays the role of bearing and transmitting stress in adhesive and is a key component affecting the performance of adhesive.
[0031] Tackifying resins such as terpene resins or rosin and its derivative resins are used to increase the viscosity or adhesion of adhesives. These resins can improve the wettability and fluidity of adhesives, thereby improving their initial tack and bonding properties. Terpene resins are well soluble in various acrylic acids in solvent-based acrylic adhesives, and have significantly improved docking strength and cohesion.
[0032] Curing agents are substances that cause the polymers in the adhesive to undergo cross-linking reactions, thereby increasing the cohesion and heat resistance of the adhesive. Curing agents can be isocyanate or epoxy curing agents. Isocyanate curing agents react with hydroxyl groups or other active groups in the adhesive to form strong chemical bonds, thereby increasing the bonding strength and heat resistance of the adhesive. Epoxy curing agents react with epoxy groups to form a three-dimensional network structure, thereby increasing the cohesive strength of the adhesive. Solvents are used to adjust the viscosity and process properties of the adhesive, making it easier to apply and operate.
[0033] The above components work together to make the thermal debonding adhesive have good bonding properties. At the same time, it can be easily removed from the bonding surface by thermal debonding when necessary, making it suitable for specific industrial applications.
[0034] In the preparation of modified polyacrylic acid resin, hydroxyethyl acrylate is used as a reactive monomer, which contains hydroxyl and acrylic acid groups, and di-tert-butyl dicarbonate is used to react with hydroxyethyl acrylate to introduce additional functional groups to change the molecular structure of the resin and improve the performance of the resin. 4-Dimethylaminopyrrolidone is used as an auxiliary agent to promote the reaction between hydroxyethyl acrylate and di-tert-butyl dicarbonate and increase the reaction rate or selectivity.
[0035] Toluene as a solvent provides a homogeneous reaction medium, allowing the reactants to mix and react thoroughly. The volatility of toluene also facilitates the subsequent drying and concentration steps.
[0036] Chloroform is used as a diluent to reduce the viscosity of the reaction mixture, facilitating subsequent washing and separation steps.
[0037] Dilute hydrochloric acid is used to wash the organic phase to remove residual impurities and inorganic salts and improve the purity of the product.
[0038] Tert-butyl acrylate and isooctyl acrylate are used to copolymerize with modified monomers to form modified polyacrylic acid resins. They provide additional functional groups and different side chain structures, which affect the final properties of the resin, such as adhesion, flexibility, etc. Azobisisobutyronitrile is used as an initiator, which generates free radicals in the polymerization reaction, triggering the polymerization of acrylic acid monomers to form the polymer chain of the resin.
[0039] Anisole is used as a solvent for polymerization, which provides a uniform reaction medium and plays a role in controlling the reaction rate and polymer molecular weight during the polymerization process. Inert atmospheres such as nitrogen or argon are used to exclude oxygen and other gases that may affect the polymerization reaction and prevent oxidation or degradation of the reaction system.
[0040] Through the synergistic effect of the above components, the prepared modified polyacrylic acid resin has a specific chemical structure and functional groups, which gives it excellent bonding properties and thermal debonding properties, and is suitable for the production of thermal debonding glue.
[0041] Example 1
[0042] A method for preparing pyrolytic adhesive water comprises the following steps, measured in parts by weight:
[0043] 90 parts of modified polyacrylic acid resin, 20 parts of terpene resin, 2 parts of isocyanate curing agent and 80 parts of ethyl acetate are mixed evenly to obtain pyrolytic adhesive.
[0044] The preparation method of the modified polyacrylate resin comprises the following steps, calculated in parts by weight:
[0045] X1. Add hydroxyethyl acrylate, di-tert-butyl dicarbonate and 4-dimethylaminopyridine to toluene at a molar ratio of 1:1:0.1, wherein the volume of toluene is the sum of the volumes of hydroxyethyl acrylate, di-tert-butyl dicarbonate and 4-dimethylaminopyridine. Stir at room temperature for 24 hours, add chloroform 4 times the volume of toluene to dilute, and then wash with 0.1 mol / L dilute hydrochloric acid. After separation, the organic phase is dried, concentrated and purified by column to obtain a modified monomer.
[0046] X2. Add the modified monomer and tert-butyl acrylate, isooctyl acrylate and azobisisobutyronitrile to anisole in a molar ratio of 6:6:4:0.1, wherein the volume of anisole is 3 times the total volume of the modified monomer and tert-butyl acrylate, isooctyl acrylate and azobisisobutyronitrile. Heat to 60°C under a nitrogen atmosphere for polymerization. After 3 hours, purify by column to remove impurities and solvent to obtain modified polyacrylic acid resin.
[0047] Example 2
[0048] A method for preparing pyrolytic adhesive water comprises the following steps, measured in parts by weight:
[0049] 93 parts of modified polyacrylic acid resin, 20 parts of terpene resin, 2 parts of isocyanate curing agent and 80 parts of ethyl acetate are mixed evenly to obtain pyrolytic adhesive.
[0050] The preparation method of the modified polyacrylate resin comprises the following steps, calculated in parts by weight:
[0051] X1. Add hydroxyethyl acrylate, di-tert-butyl dicarbonate and 4-dimethylaminopyridine to toluene at a molar ratio of 1:1:0.1, wherein the volume of toluene is the sum of the volumes of hydroxyethyl acrylate, di-tert-butyl dicarbonate and 4-dimethylaminopyridine. Stir at room temperature for 24 hours, add chloroform 4 times the volume of toluene to dilute, and then wash with 0.1 mol / L dilute hydrochloric acid. After separation, the organic phase is dried, concentrated and purified by column to obtain a modified monomer.
[0052] X2. Add the modified monomer and tert-butyl acrylate, isooctyl acrylate and azobisisobutyronitrile to anisole in a molar ratio of 6:6:4:0.1, wherein the volume of anisole is 3 times the total volume of the modified monomer and tert-butyl acrylate, isooctyl acrylate and azobisisobutyronitrile. Heat to 60°C under a nitrogen atmosphere for polymerization. After 3 hours, purify by column to remove impurities and solvent to obtain modified polyacrylic acid resin.
[0053] Example 3
[0054] A method for preparing pyrolytic adhesive water comprises the following steps, measured in parts by weight:
[0055] 95 parts of modified polyacrylic acid resin, 20 parts of terpene resin, 2 parts of isocyanate curing agent and 80 parts of ethyl acetate are mixed evenly to obtain pyrolytic adhesive.
[0056] The preparation method of the modified polyacrylate resin comprises the following steps, calculated in parts by weight:
[0057] X1. Add hydroxyethyl acrylate, di-tert-butyl dicarbonate and 4-dimethylaminopyridine to toluene at a molar ratio of 1:1:0.1, wherein the volume of toluene is the sum of the volumes of hydroxyethyl acrylate, di-tert-butyl dicarbonate and 4-dimethylaminopyridine. Stir at room temperature for 24 hours, add chloroform 4 times the volume of toluene to dilute, and then wash with 0.1 mol / L dilute hydrochloric acid. After separation, the organic phase is dried, concentrated and purified by column to obtain a modified monomer.
[0058] X2. Add the modified monomer and tert-butyl acrylate, isooctyl acrylate and azobisisobutyronitrile to anisole in a molar ratio of 6:6:4:0.1, wherein the volume of anisole is 3 times the total volume of the modified monomer and tert-butyl acrylate, isooctyl acrylate and azobisisobutyronitrile. Heat to 60°C under a nitrogen atmosphere for polymerization. After 3 hours, purify by column to remove impurities and solvent to obtain modified polyacrylic acid resin.
[0059] Example 4
[0060] A method for preparing pyrolytic adhesive water comprises the following steps, measured in parts by weight:
[0061] 90 parts of modified polyacrylic acid resin, 15 parts of terpene resin, 2 parts of isocyanate curing agent and 80 parts of ethyl acetate are mixed evenly to obtain pyrolytic adhesive.
[0062] The preparation method of the modified polyacrylate resin comprises the following steps, calculated in parts by weight:
[0063] X1. Add hydroxyethyl acrylate, di-tert-butyl dicarbonate and 4-dimethylaminopyridine to toluene at a molar ratio of 1:1:0.1, wherein the volume of toluene is the sum of the volumes of hydroxyethyl acrylate, di-tert-butyl dicarbonate and 4-dimethylaminopyridine. Stir at room temperature for 24 hours, add chloroform 4 times the volume of toluene to dilute, and then wash with 0.1 mol / L dilute hydrochloric acid. After separation, the organic phase is dried, concentrated and purified by column to obtain a modified monomer.
[0064] X2. Add the modified monomer and tert-butyl acrylate, isooctyl acrylate and azobisisobutyronitrile to anisole in a molar ratio of 6:6:4:0.1, wherein the volume of anisole is 3 times the total volume of the modified monomer and tert-butyl acrylate, isooctyl acrylate and azobisisobutyronitrile. Heat to 60°C under a nitrogen atmosphere for polymerization. After 3 hours, purify by column to remove impurities and solvent to obtain modified polyacrylic acid resin.
[0065] Example 5
[0066] A method for preparing pyrolytic adhesive water comprises the following steps, measured in parts by weight:
[0067] 90 parts of modified polyacrylic acid resin, 25 parts of terpene resin, 2 parts of isocyanate curing agent and 80 parts of ethyl acetate are mixed evenly to obtain pyrolytic adhesive.
[0068] The preparation method of the modified polyacrylate resin comprises the following steps, calculated in parts by weight:
[0069] X1. Add hydroxyethyl acrylate, di-tert-butyl dicarbonate and 4-dimethylaminopyridine to toluene at a molar ratio of 1:1:0.1, wherein the volume of toluene is the sum of the volumes of hydroxyethyl acrylate, di-tert-butyl dicarbonate and 4-dimethylaminopyridine. Stir at room temperature for 24 hours, add chloroform 4 times the volume of toluene to dilute, and then wash with 0.1 mol / L dilute hydrochloric acid. After separation, the organic phase is dried, concentrated and purified by column to obtain a modified monomer.
[0070] X2. Add the modified monomer and tert-butyl acrylate, isooctyl acrylate and azobisisobutyronitrile to anisole in a molar ratio of 6:6:4:0.1, wherein the volume of anisole is 3 times the total volume of the modified monomer and tert-butyl acrylate, isooctyl acrylate and azobisisobutyronitrile. Heat to 60°C under a nitrogen atmosphere for polymerization. After 3 hours, purify by column to remove impurities and solvent to obtain modified polyacrylic acid resin.
[0071] Comparative Example 1
[0072] A method for preparing pyrolytic adhesive water comprises the following steps, measured in parts by weight:
[0073] 90 parts of polyacrylic acid resin, 25 parts of terpene resin, 2 parts of isocyanate curing agent and 80 parts of ethyl acetate are mixed evenly to obtain pyrolytic adhesive.
[0074] The preparation method of the polyacrylate resin comprises the following steps, measured in parts by weight:
[0075] Tert-butyl acrylate, isooctyl acrylate and azobisisobutyronitrile were added to anisole in a molar ratio of 12:4:0.1, the volume of anisole was 3 times the total volume of tert-butyl acrylate, isooctyl acrylate and azobisisobutyronitrile, the temperature was raised to 60°C under a nitrogen atmosphere for polymerization, and after 3 hours, the modified polyacrylic acid resin was obtained after column purification to remove impurities and solvents.
[0076] Comparative Example 2
[0077] A method for preparing pyrolytic adhesive water comprises the following steps, measured in parts by weight:
[0078] 90 parts of modified polyacrylic acid resin, 20 parts of terpene resin, 2 parts of isocyanate curing agent and 80 parts of ethyl acetate are mixed evenly to obtain pyrolytic adhesive.
[0079] The preparation method of the modified polyacrylate resin comprises the following steps, calculated in parts by weight:
[0080] X1. Add hydroxyethyl acrylate, di-tert-butyl dicarbonate and 4-dimethylaminopyridine to toluene at a molar ratio of 1:1:0.1, wherein the volume of toluene is the sum of the volumes of hydroxyethyl acrylate, di-tert-butyl dicarbonate and 4-dimethylaminopyridine. Stir at room temperature for 24 hours, add chloroform 4 times the volume of toluene to dilute, and then wash with 0.1 mol / L dilute hydrochloric acid. After separation, the organic phase is dried, concentrated and purified by column to obtain a modified monomer.
[0081] X2. Add the modified monomer, isooctyl acrylate and azobisisobutyronitrile to anisole in a molar ratio of 12:4:0.1, wherein the volume of anisole is 3 times the total volume of the modified monomer, isooctyl acrylate and azobisisobutyronitrile. Heat to 60°C in a nitrogen atmosphere for polymerization. After 3 hours, purify by column to remove impurities and solvent to obtain modified polyacrylic acid resin.
[0082] Test Example 1
[0083] The peel strength of the pyrolytic adhesive prepared in the embodiment and the control example was tested before and after heat treatment. The 180° peel strength of the adhesive before thermal debonding and the 180° peel strength after treatment at 80°C and 150°C were tested with reference to GB / T 2792-2014 "Test method for peel strength of adhesive tape". The specific results are shown in Table 1.
[0084] Table 1 Peel force test results of pyrolysis adhesive Experimental protocol Peeling force before heat treatment / N / 25mm Peel force after 80℃ treatment / N / 25mm Peel force after 150℃ treatment / N / 25mm Example 1 10.12 7.12 0.46 Example 2 9.56 6.73 0.51 Example 3 9.67 6.80 0.47 Example 4 9.56 6.93 0.48 Example 5 9.66 6.89 0.58 Comparative Example 1 9.56 2.13 0.34 Comparative Example 2 9.47 7.89 5.76
[0085] As can be seen from Table 1, the thermal debonding glue prepared by the present invention has good adhesion. After high-temperature treatment, the adhesion has decreased to varying degrees. Compared with the comparative example 1, the temperature required for thermal debonding is higher. The glue prepared in the comparative example 1 can achieve thermal debonding after heat treatment at 80°C. However, electronic components may generate heat during operation and reach a higher temperature. If the glue can achieve thermal debonding at a lower temperature, it may bring the risk of debonding. However, the adhesiveness of the glue prepared in Examples 1 to 5 does not decrease significantly under 80°C treatment, and still has good adhesion. This may be because the ester bond is a thermally degradable bond, and the thermal degradation ability decreases from tertiary ester to secondary ester to primary ester in sequence, while the modified polypropylene in Example 1 The acid ester contains tert-butyl ester and tert-butoxycarbonyl, among which tert-butyl ester has a higher thermal degradation ability, but the thermal degradation of tert-butoxycarbonyl requires a relatively high temperature. Therefore, the modified polyacrylic resin obtained is not easy to debond at a lower temperature. The polyacrylate in Control Example 1 only has tert-butyl ester as a thermal degradation group, and the modified polyacrylate in Control Example 2 only has tert-butoxycarbonyl as a thermal degradation group. Therefore, the glue in Control Example 1 will debond after being treated at 80°C, which also means that the glue may debond at temperatures below 80°C. The glue in Control Example 2 still does not debond after being treated at 150°C and still has good adhesion, which means that the glue requires a higher thermal debonding temperature, which is not conducive to practical application. Compared with Examples 2 to 5, the amount of modified polyacrylate and tackifying resin used in Example 1 is different. As the basic component of the pyrolytic adhesive in the glue, the tackifying resin provides the main bonding performance. The tackifying resin is used to improve the viscosity of the glue to ensure that it has good adhesion on different material surfaces. These resins improve the initial adhesion and peeling force of the glue by forming a hydrogen bond network structure. When the amount of modified polyacrylate and tackifying resin used is different, the bonding performance of the glue is also different. From the data in Table 1, it can be seen that the bonding performance of the glue in Example 1 is the best.
[0086] Test Example 2
[0087] The glue prepared in the examples and the comparative examples was subjected to a residual glue test, where the glue was attached to a peeling board and torn off at a constant speed, and the residual glue or residue area was calculated and expressed as a percentage. The specific results are shown in Table 2.
[0088] Table 2 Test results of residual adhesiveness of pyrolysis adhesive water Experimental protocol Residue or residue area / % Example 1 <1 Example 2 <1 Example 3 <1 Example 4 <1 Example 5 <1 Comparative Example 1 <1 Comparative Example 2 <1
[0089] When a heat-sensitive expansion material is added to the glue, the glue is heated to a higher temperature, so that the heat-sensitive expansion material expands and increases in volume, thereby reducing the effective contact area with the adhered object and reducing the peel strength. However, as a nanomaterial, the heat-expanding additive is easy to remain on the surface of the substrate, resulting in residual glue. Compared with thermal expansion debonding, thermal degradation debonding reduces the modulus and molecular weight of the adhesive, resulting in a reduction in its bonding strength, and does not require the participation of additives. Therefore, the probability of residual glue in the heat-debonded glue prepared by the present invention is very low.
[0090] The preferred specific embodiments of the present invention are described in detail above. It should be understood that a person skilled in the art can make many modifications and changes based on the concept of the present invention without creative work. Therefore, any technical solution that can be obtained by a person skilled in the art through logical analysis, reasoning or limited experiments based on the concept of the present invention on the basis of the prior art should be within the scope of protection determined by the claims.
Claims
1. A pyrolytic adhesive, characterized in that: The invention comprises the following components in parts by weight: 90-95 parts of modified polyacrylic acid resin, 15-35 parts of tackifying resin, 1-3 parts of curing agent and 80-85 parts of solvent.
2. The pyrolysis adhesive according to claim 1, characterized in that: The preparation method of the modified polyacrylate resin comprises the following steps: X1. Add hydroxyethyl acrylate, di-tert-butyl dicarbonate and 4-dimethylaminopyridine to toluene, stir at room temperature, add chloroform to dilute, and wash with dilute hydrochloric acid. After separation, the organic phase is dried, concentrated and purified by column to obtain a modified monomer; X2. Add the modified monomer, tert-butyl acrylate, isooctyl acrylate and azobisisobutyronitrile to anisole, heat and polymerize under an inert atmosphere, and purify by column to remove impurities and solvent to obtain modified polyacrylic acid resin.
3. The pyrolysis adhesive according to claim 2, characterized in that: Furthermore, the molar ratio of the hydroxyethyl acrylate to di-tert-butyl dicarbonate and 4-dimethylaminopyridine is 1:1-2:0.1-0.
2.
4. The pyrolytic adhesive according to claim 2, characterized in that: Furthermore, the molar ratio of the modified monomer to tert-butyl acrylate, isooctyl acrylate, and azobisisobutyronitrile is 5-9:5-9:4-10:0.1-0.
2.
5. The pyrolytic glue solution as claimed in claim 2, characterized in that: The temperature range of the temperature-raising polymerization is 60-80°C.
6. The pyrolytic adhesive according to claim 1, characterized in that: The tackifying resin is one of terpene and its derivative resins, rosin and its derivative resins.
7. The pyrolytic adhesive according to claim 1, characterized in that: The curing agent is one of an isocyanate curing agent and an epoxy curing agent.
8. The pyrolytic adhesive according to claim 1, characterized in that: The solvent is one of ethyl acetate, toluene or isopropanol.
9. A method for preparing the pyrolytic adhesive water according to any one of claims 1 to 8, characterized in that: The steps include: 90 parts of modified polyacrylic acid resin, tackifying resin, curing agent and solvent are uniformly mixed to obtain pyrolytic adhesive.
10. Use of the pyrolytic adhesive water as claimed in claim 1 in cutting electrolytic membranes.
Citation Information
Patent Citations
Thermal visbreaking polyacrylate pressure-sensitive adhesive and preparation method thereof
CN118389098A
Radiation-curable coatings for wood substrates from multifunctional acrylate oligomers
CN101006103A
Hard coating composition and hard coating film using the same
CN107400389A
Thermal visbreaking adhesive, thermal visbreaking protective film and preparation method
CN114989778A
Pyrolytic adhesive and pyrolytic adhesive foam tape containing same
CN117447934A
